2021
DOI: 10.3389/fmolb.2021.655580
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-653-5p Promotes Gastric Cancer Proliferation and Metastasis by Targeting the SOCS6-STAT3 Pathway

Abstract: MicroRNAs (miRNAs) are emerging as significant regulators of the tumorigenesis of gastric cancer (GC), and may be effective biomarkers for diagnosis, prognosis, and therapeutic targeting for GC. In this study, miR-653-5p was found to be significantly upregulated in GC tissues, serum, and cell lines and was strongly associated with poor prognosis in patients with GC. Furthermore, miR-653-5p promoted GC cell proliferation and metastasis in vivo and in vitro. Suppressor of cytokine signaling 6 (SOCS6) was directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…Notably, recent studies have shown that SOCS6 can act as a negative regulator of the STAT3 signaling pathway, promoting epidermal stem cell differentiation and regulating apoptosis of vascular endothelial cells by increasing the ubiquitination of JAK2 and inhibiting the activation of the JAK2/STAT3 pathway 53,54 . Moreover, some miRNAs, such as miR‐19, miR‐653‐5p, and miR‐548d‐3p, have been shown to promote tumorigenesis by targeting SOCS6 and reversing the inhibitory effect of SOCS6 on STAT3 signaling 49,55,56 . Interestingly, our study also revealed that overexpression of SOCS6 could significantly decrease the expression level of p‐STAT3, while miR‐296‐3p greatly increased the expression of p‐STAT3 by targeting SOCS6, suggesting that miR‐296‐3p promoted activation of the downstream STAT3 signaling pathway in ovarian cancer by targeting SOCS6.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Notably, recent studies have shown that SOCS6 can act as a negative regulator of the STAT3 signaling pathway, promoting epidermal stem cell differentiation and regulating apoptosis of vascular endothelial cells by increasing the ubiquitination of JAK2 and inhibiting the activation of the JAK2/STAT3 pathway 53,54 . Moreover, some miRNAs, such as miR‐19, miR‐653‐5p, and miR‐548d‐3p, have been shown to promote tumorigenesis by targeting SOCS6 and reversing the inhibitory effect of SOCS6 on STAT3 signaling 49,55,56 . Interestingly, our study also revealed that overexpression of SOCS6 could significantly decrease the expression level of p‐STAT3, while miR‐296‐3p greatly increased the expression of p‐STAT3 by targeting SOCS6, suggesting that miR‐296‐3p promoted activation of the downstream STAT3 signaling pathway in ovarian cancer by targeting SOCS6.…”
Section: Discussionsupporting
confidence: 62%
“…[48][49][50][51] However, the roles and specific mo- versing the inhibitory effect of SOCS6 on STAT3 signaling. 49,55,56 Interestingly, our study also revealed that overexpression of SOCS6 could significantly decrease the expression level of p-STAT3, while miR-296-3p greatly increased the expression of p-STAT3 by targeting SOCS6, suggesting that miR-296-3p promoted activation of the downstream STAT3 signaling pathway in ovarian cancer by targeting SOCS6. serve as an early diagnostic marker for patients with ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Extracted proteins were separated by sodium dodecyl sulfate–polyacrylamide gel electrophoresis and transferred to polyvinylidene difluoride (PVDF) membranes. The relative expression of proteins was determined using an ECL detection system ( Li et al, 2021 ). The primary antibodies were those against GR (Cell Signaling Technology, Danvers, MA, United States), p-GR (Ser211; Cell Signaling Technology), SOCS3 (Thermo Scientific), and STAT3 (124H6; Cell Signaling Technology).…”
Section: Methodsmentioning
confidence: 99%
“…For example, a significant difference in the expression levels of miR199a-3p, miR-451 and other miRNAs was found between cancer patients and normal controls [ 56 , 57 ] A significant correlation has been reported between patient prognosis and miRNAs miR-21 and miR-200c, which indicates that miRNAs can be used as prognostic markers [ 58 , 59 ]. MiRNAs can not only be used as biomarkers of gastric cancer, but also affect Akt and Akt, NF-κB, RAGE, ARF6, TCF4, STAT3 and other signaling pathways promote or inhibit the occurrence and development of gastric cancer [ 69 , 70 , 73 76 ]. In the meantime, miRNAs can also alter lipid metabolism, energy metabolism and amino acid metabolism, thus indirectly affecting the occurrence and development of cancer [ 80 82 ].…”
Section: Perspectivementioning
confidence: 99%